Analysis of global, regional and national trends in the burden of soft tissue and other extraosseous sarcomas from 1990 to 2021: A systematic analysis of the global burden of disease study 2021 - Xing Chen; Zhixiong Zhang; Jiwei Xiang; Ruliu Xiong; Xingmao Zhou (PLoS ONE, 2025)
Background Soft tissue and other extraosseous sarcomas (STSES) are rare malignant tumors originating from mesenchymal tissues with complex etiologies. A systematic analysis of global burden trends is urgently needed. Methods Utilizing the Global Burden of Disease (GBD) 2021 database, we assessed STSES incidence, mortality, disability-adjusted life years (DALYs), age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR) across regions and countries from 1990 to 2021, stratified by sociodemographic index (SDI). Spatiotemporal models, Joinpoint regression (to calculate average annual percentage changes, AAPC), and decomposition analysis were employed to evaluate the impacts of population growth, aging, and epidemiological factors on disease burden. Results In 2021, there were 96,201 new STSES cases globally, resulting in 50,203 deaths and 1.678 million DALYs. While age-standardized rates (per 100,000 person-years) showed declining trends (AAPC for ASIR = −0.13, ASMR = −0.60, ASDR = − 0.94), absolute burden increased by 77.97% due to population growth. Males exhibited consistently higher burden than females, with incidence peaking at 55–74 years. Notably, young females (10–29 years) transiently surpassed males in DALYs. Significant regional disparities emerged: High-SDI regions (e.g., Western Europe) demonstrated lower ASMR attributable to advanced diagnostics and treatment, whereas low-SDI regions (e.g., Uganda, ASMR = 1.96/100,000) faced poorer prognoses due to healthcare deficiencies. SDI exhibited a nonlinear association with disease burden—middle-SDI regions (0.4–0.8) showed rising ASIR, potentially linked to industrial pollution and improved diagnostic capabilities. These findings underscore the critical need for context-specific prevention and resource allocation strategies to address the evolving global STSES burden. Conclusions The global STSES burden is predominantly driven by population growth, necessitating targeted prevention strategies addressing occupational exposures in males and subtype-specific risks among young females. While high-SDI regions demonstrate mortality reduction through precision oncology, low-SDI regions require urgent improvements in healthcare accessibility to mitigate survival disparities. Persistent regional heterogeneity underscores the imperative for international collaboration to standardize diagnostic protocols and ensure equitable resource allocation. These insights emphasize the need for stratified surveillance systems and translational research to optimize context-specific intervention frameworks.